PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT Duta Oktan Semesta Palembang) - Rini Rini; Dibyantoro Dibyantoro; M.Ihsan Ardianto (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
This research was conducted at PT Duta Oktan Semesta Palembang. This study uses compensation as an independent variable, motivation as an intervening variable and performance as the dependent variable.  The purpose of this study was to analyze the effect of compensation on employee performance through employee motivation as an intervening variable.  The sample used was an employee of PT Duta Oktan Semesta Palembang set the number of samples in this study were 42 respondents.  The analysis includes the validity test, reliability test, the classic assumption test, test models, regression analysis and path analysis. Based on the results of two regression analyzes can be performed so that the path analysis found that the variable motivation to become an intervening variable is based on the calculation of the standardized coefficients for the indirect effect of compensation on performance through employee motivation at 48.1% greater than the direct effect of compensation on performance of 24.3%.  The author concluded that the company should increase the motivation of employees to improve their performance.